Epidemics in Motion. Exploring the Interaction between Childhood Diseases in a Norwegian City, 1863–1928 - Sommerseth, Hilde Leikny; Walhout, Evelien (Historical Life Course Studies, 2025)
This article explores interactions between measles and whooping cough in Christiania (now Oslo) during the period 1863–1928, using annual morbidity, mortality, and fertility data. Drawing on the ecological interference model proposed by Rohani et al. (2003), we examine whether epidemic patterns shifted from so-called out-of-phase to in-phase dynamics as fertility declined and the pool of susceptibles decreased. Dividing the analysis into two periods based on crude birth rates, we find that during the high-fertility era, disease cycles were typically out of phase. Surprisingly, this dynamic persists even in a period with comparatively lower birth rates, contradicting theoretical expectations. We discuss potential explanations, including population size thresholds for transmission and limitations in the available data. Modest in scope but exploratory in spirit, the study contributes to ongoing efforts - such as those initiated by Angélique Janssens — to use historical health data to understand long-term epidemic dynamics and inter-disease relationships.